Regulations and Implementation of the Green Economy in the Development of Green SMEs in North Sumatra Province - Putriyanda, Diennissa; Sirait, Ningrum Natasya; Lubis, Tri Murti (Al-Bayyinah, 2025)
This research analyzes the regulation and implementation of a green economy in the MSME sector in North Sumatra Province in the context of the transition to green MSMEs and efforts to achieve the Sustainable Development Goals (SDGs). This study uses a combination of normative and empirical approaches with data collected through interviews, questionnaires, and literature studies. The findings indicate that North Sumatra Province has not specifically adopted and implemented a green economy for the MSME sector. In the North Sumatra Provincial RPJPD 2025-2045, the implementation of a green economy is still limited to Green Industry. The absence of regulations, the lack of updates on the Regional Action Plan for TPB/SDGs, and the fragmented coordination among key stakeholders, who still do not have a structured collaboration framework, pose the main obstacles. SMEs in North Sumatra Province face various challenges in implementing a green economy, including high investment costs, limited access to resources, the absence of regulations and standards, and a lack of consumer awareness about eco-friendly products. This research recommends that the North Sumatra Provincial Government prioritize the integration of the SDGs into regional development policies, establish regulations that govern coordination among stakeholders, and enhance government and stakeholder support for the green transformation of SMEs through improved access to resources, training, and policy support.